2016
DOI: 10.1090/conm/676/13608
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Metric Spaces and the Gromov-Hausdorff Propinquity

Abstract: We present a survey of the dual Gromov-Hausdorff propinquity, a noncommutative analogue of the Gromov-Hausdorff distance which we introduced to provide a framework for the study of the noncommutative metric properties of C*-algebras. We first review the notions of quantum locally compact metric spaces, and present various examples of such structures. We then explain the construction of the dual Gromov-Hausdorff propinquity, first in the context of quasi-Leibniz quantum compact metric spaces, and then in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In this section we work in the framework of Gromov-Hausdorff propinquity developed by Latrémolière recently in [Lat15a,Lat16,Lat15b]. We will show that our previous results on convergence of matrix algebras to rotation algebras actually hold in the strong sense of (1) For all a ∈ A such that |||a||| A ≤ 1, there exists b ∈ B such that |||b||| B ≤ 1 and…”
Section: Application To Gromov-hausdorff Propinquitymentioning
confidence: 90%
See 3 more Smart Citations
“…In this section we work in the framework of Gromov-Hausdorff propinquity developed by Latrémolière recently in [Lat15a,Lat16,Lat15b]. We will show that our previous results on convergence of matrix algebras to rotation algebras actually hold in the strong sense of (1) For all a ∈ A such that |||a||| A ≤ 1, there exists b ∈ B such that |||b||| B ≤ 1 and…”
Section: Application To Gromov-hausdorff Propinquitymentioning
confidence: 90%
“…Θ n (n) in Proposition 7.5. By Definition 2.21 in [Lat15a] and the existence of a derivation δ as defined in (3.4), (A 2d Θ , |||.|||) and (A 2d Θ n (n), |||.|||) are Leibniz pairs. Indeed, the conditions in the definition were proved in [JM10,JMP14]; see also [Zen14] for more remarks on the Lip-norms.…”
Section: Recall the Definition Of A 2dmentioning
confidence: 99%
See 2 more Smart Citations
“…where the object on the right-hand side is a · A Θ -compact subset of A Θ (see [5,Remark 2.46]). Hence, as X ∈ D 1 g is arbitrary, we have shown that there exists a single · A Θ -compact subset of A Θ that contains the A Θ -coefficients of all elements of D 1 g , which implies that D 1 g is · st -precompact in χ Θ .…”
Section: Huangmentioning
confidence: 99%